Propagation of laser modes by testing the angular spectrum technique and the analysis of Gaussian beam profiles by using the multiple knife-edge method - Talatinian, Alexander (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
This research focuses on the analysis of laser beam shape propagation properties and the generalized beam shaping of the fundamental Gaussian mode, Hermite–Gaussian modes and Laguerre–Gaussian modes, which were studied analytically and numerically using the angular spectrum technique and the 2D fast Fourier transformation procedures. The fundamental Gaussian mode is applied here as the reference for checking the accuracy of beam profile analysis based on multiple scanning knife-edge method. A set of spatial profile curves is generated, each of which represents the intensity profile of the fundamental Gaussian mode for different directions of propagation. The He-Ne laser and the diode laser are used as the probe lasers. The experimental results show that the He-Ne laser emits a pure fundamental Gaussian mode, whereas the diode laser emits an elliptical beam shape. Some numerical simulation examples of the generated beams are also given to illustrate the propagation properties of the fundamental Gaussian mode, Hermite–Gaussian modes, and Laguerre–Gaussian modes.
Optica Applicata, Vol. 54, 2024, nr 3, s. 283-302
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; laser beam analysis; multiple knife-edge; propagation of higher modes; ngular spectrum algorithm